Data for Permafrost Degradation Diminishes Terrestrial Ecosystem Carbon Sequestration Capacity on the Qinghai-Tibetan Plateau [version 1.0] - Dan Kou; Dongsheng Zhao; Du Zheng; Lei Liu; Qianlai Zhuang; Yuanhe Yang (2021)
Effects of permafrost degradation on carbon (C) and nitrogen (N) cycling on the Qinghai-Tibetan Plateau (QTP) have rarely been analyzed. This study used a revised process-based biogeochemical model to quantify the effects in the region during the 21st century. Permafrost degradation would expose 0.98±0.49 (mean±SD) and 2.17±0.38 Pg C of soil organic carbon under the representative concentration pathway (RCP) 4.5 and the RCP 8.5, respectively. Among them, more than 25% will be decomposed, enhancing heterotrophic respiration by 9.54±5.20 (RCP 4.5) and 38.72±17.49 (RCP 8.5) Tg C/yr in 2099. Deep soil N supply due to thawing permafrost is not accessible to plants, providing limited benefits to plant growth and only stimulating net primary production by 6.95±5.28 (RCP 4.5) and 27.97±12.82 (RCP 8.5) Tg C/yr in 2099. As a result, permafrost degradation would weaken the regional C sink (net ecosystem production) by 303.55±254.80 (RCP 4.5) and 518.43±234.04 (RCP 8.5) Tg C cumulatively during 2020–2099. This dataset includes the main results of this study. The Terrestrial Ecosystem Model (TEM) was adopted in this study to account for the effects of exposed permafrost C and N to ecosystem C cycling in the permafrost region on the QTP. TEM was driven with spatially referenced climate data from 2006 to 2099, including air temperature (℃), precipitation (mm), and incident short-wave solar radiation (W/m2). These data were derived from four global circulation models (GCMs: IPSL-CM5A-LR, GFDL-ESM2M, MIROC5, and HadGEM2-ES) in the second simulation round of the Inter-Sectoral Impact Model Intercomparison Project (ISI-MIP 2b). And the simulation was conducted under two climate scenarios of the Representative Concentration Pathway 4.5 (RCP 4.5) and RCP 8.5, which correspond to radiative forcing levels of 4.5 and 8.5 W/m2 by 2100, respectively. To determine the direct effects of ALT deepening on ecosystem C dynamics, we carried out two simulations: the referenced simulation (SR) and the transient simulation (ST). The two ...